3D inversion of electromagnetic logging-while-drilling data. Issue 1 (1st December 2019) - Marchant, David; Clegg, Nigel; Rawsthorne, Luke; Kunnas, Jari
Summary: Electromagnetic logging while drilling is commonly used to infer information about the electrical properties around the wellbore and to aid in geosteering. Data from modern tools, which combine multiple transmitter and receiver orientations and offsets, can be difficult to manually interpret in all but the simplest of environments. Inversion is required to optimally extract and use the information from this data. Although low dimensional inversions can provide useful information in certain environments, full, 3D solutions are required to extract the maximum possible amount of information from the data. In this work, we present the first fully 3D inversion of electromagnetic logging-while-drilling data. Moreover, we demonstrate that using semi-structured meshing and mesh decoupling, along with advanced data integration techniques, enables the inversions to be performed in real time.